MONOSODIUM GLUTAMATE (MSG) INDUCED DEVELOPMENTAL DYSFUNCTION IN FEMALE ALBINO RATS (RATTUS NORVEGICUS - K. ROY GEORGE; N. G. SHIBIJA; N. A. MALINI (The Bioscan, 2012)
Effects of a flavor enhancer, monosodium glutamate (MSG) was evaluated in female albino rats during the gestational period. Different doses of MSG (0.4g/kg and 4g/kg body weight) were administered orally using drinking water as a vehicle for 0 -15th day of gestational period. The control received water only. On completion of the treatment period, the half of the experimental animals were sacrificed under light anesthesia using ether and the other half were allowed to deliver their pups. The body weight, the gravid uterine weight, organ weight, number of implantations, litter size, litter weight, growth rate of the viable off springs etc. were altered after MSG treatment. MSG also induced some abnormal changes in gestation such as abortion and or resorption of fetuses. The present study suggested that MSG adversely affected the fetal development of the pregnant female rats.